Co Management Health and Economic Development Indexes: Grand Strategy for Health Development in the Madura Island- Indonesia Coast through Mangrove planting - Endang Tri Wahyurini; Darsono; Kusnandar; Mohammad Harisudin (Indian Journal of Forensic Medicine & Toxicology, 2021)
Poverty in Indonesia’s coastlines is currently an unresolved national issue. This study aims to analyze themangrove co-management in the economic and health development in the coasts, as an effort to tacklepoverty. This research uses the qualitative and quantitative methods, analyzed using the SEM WarpPLS.The research results show that in the coastlines of Madura Island, the Instructive Co-Management is mostdominantly applied in managing mangroves. The mangrove co-management has positive and significanteffects towards the economic and health development of the coastlines. The economic development ofMadura Island’s coasts is marked by the increase of the people’s income, the creation of new job fields,and also the increase of health conditions, in line with the increase of mangrove preservation quality andquantity.